Perlindungan Hukum Terhadap Anak Sebagai Pelaku Tindak Pidana Pencurian - Suwarno, Muhammad (Jurnal Sosial Humaniora Sigli, 2025)
Nowadays, many cases involving children as perpetrators of criminal acts have emerged, especially in cases of theft. Many cases of criminal acts of theft in Indonesia committed by children have emerged from various regions. The problems discussed in this research are how the judge's decision to sentence children as perpetrators of criminal acts provides legal protection, especially in Decision Number 8/Pid.Sus.Anak/2024/PN Kot and Decision Number 10/Pid.Sus.Anak/2024/PN Kot? What is the ideal legal protection for children as perpetrators of criminal acts? Normative juridical research methods. In conclusion, the decisions handed down by the judge were both in decision number 8/Pid.Sus.Anak/2024/PN Kot and Decision 10/Pid.Sus.Anak/2024/PN Kot which imposed the respective sentences at the Special Child Development Institution (LPKA) , has reflected the form of legal protection itself for children who commit crimes of theft. The ideal legal protection for children who commit criminal acts of theft is based on Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, namely that children as perpetrators of criminal acts of theft receive protection from reporting their identity through mass media and to avoid labeling, receive diversion efforts, assistance from parents, social services and community centers, receive an investigation process in a family atmosphere, places of detention or imprisonment are separated from places for adults, children's physical, spiritual and social needs are met, health insurance is provided, education is provided, and avoidance of torture and harassment, providing accessibility, case examination and special investigators in the process of handling children.Keywords : Legal Protection, Children, Theft